Optimized properties of ZnO nanorod arrays grown on graphene oxide seed layer by combined chemical and electrochemical approach. Issue 15 (15th November 2016) - Pruna, A.; Shao, Q.; Kamruzzaman, M.; Zapien, J.A.; Ruotolo, A.
Abstract: Novel hybrid architectures based on ZnO nanostructures supported on reduced graphene oxide films are reported by a facile two-step aqueous electrochemical approach. Graphene oxide (GO) obtained by oxidizing graphite with either H2 SO4 :H3 PO4 mix or H2 SO4 was subjected to electrochemical reduction (ErGO) by constant potential and sweeping potential methods and further employed as seeding layer for electrodeposition of ZnO nanorods. The results showed the GO reduction rate was markedly influenced by oxygen content while Infrared spectroscopy indicated the sweeping potential was effective in removing the carbonyl and alkoxy groups but also as more defect-inducing reduction approach than constant potential, according to the Raman measurements. The subsequent electroreduction of ErGO during the electrodeposition of ZnO resulted in interfacial interaction between the seed layer and ZnO nanorods. H2 SO4 :H3 PO4 mix induced a less disrupted graphitic plane in GO which proved beneficial for the growth of higher density ZnO nanorods with improved crystalline quality. By controlling the chemical introduction/electroreduction conditions for oxygen groups in GO materials, the interfacial interaction with ZnO nanorods and their properties could be tailored in order to obtain high performance nanoplatforms.